Քեմփ–Դևիդի (1979թ.) ժառանգությունը. Իսրայելի հետ արաբական երկրների անհատական խաղաղության հաստատման հետագա փորձերը - Անդրանիկ Առաքելյան (ՀՀ ԳԱԱ հրատ.)
Египет первым нарушил провозглашенный в 1967 г. в Хартумской декларации принцип «трех нет». Неоднократные попытки политического диалога между Израилем и Сирией, предпринимавшиеся с января 1982 г. по март 2000 г., закончились провалом. Мирное соглашение между Иорданией и Израилем было подписано 26 октября 1994 г. уже после заключения Декларации принципов мирного урегулирования между Израилем и ООП (октябрь 1993 г.). There were several peace plans following the 1967 war, but nothing happened until the historic visit to Jerusalem by the Egyptian President, Anwar Sadat, in November 1977. This was the beginning of the first recognition of Israel as a state by a major Arab country. Other efforts were made after by Syria, Lebanon and Jordan. The Israel–Jordan peace treaty was signed in 1994. Jordan was the second Arab country, after Egypt, to sign a peace accord with Israel.
Keywords: Political Science; International relations